Disease awareness and experience of adolescent depression patients: a meta-synthesis of qualitative studies - Gao, Pei; Guo, Fan; Xu, Yanrong; Wang, Yue; Cui, Liping (Frontiers in Psychiatry, 2025)
Clinical trial registrationTo systematically evaluate the cognition and real experience of adolescent patients with depression towards the disease, in order to comprehensively understand the cognitive and psychological predicaments they face and provide a basis for formulating targeted intervention strategies for adolescent patients with depression.DesignA systematic review and meta-synthesis of qualitative studies.MethodsQualitative studies on the cognition and real experience of adolescent patients with depression towards the disease were retrieved from Chinese and English databases from the establishment of the databases to June 2025. The quality of the literature was evaluated using the JBI qualitative research quality evaluation standard, and the convergent meta-synthesis method was used for integration.ResultsA total of 12 articles were included, and 37 research results were extracted. Two themes and nine sub-themes were identified, namely, cognition of the disease (misunderstanding of the disease, stigma towards the disease, and cognition of the prognosis of the disease), and real experience of the illness (diversity of influencing factors of the illness, somatization symptoms after the illness, emotional and psychological experiences after the illness, reconstruction of interpersonal relationships, predicaments and powerlessness in treatment, and establishment of new values).ConclusionTeenagers with depression often have cognitive biases and undergo complex, multi-dimensional painful experiences. Healthcare professionals should first assess and restructure the patients’ cognitive biases and provide targeted treatment for their painful experiences. At the same time, scientific disease cognition and intervention strategies should be extended from hospitals to families and schools, and a collaborative support system should be established to jointly address the psychological needs of adolescent patients.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view, identifier CRD420251105051.